Screen time and its association with adolescents' lifestyles in a city in the Brazilian Northeast (Research, Society and Development, 2022)
Objective: To associate screen time with food, physical activity, sleep and sociodemographic variables in Brazilian adolescents, students of urban public institutions. Methods: Observational, cross-sectional, quantitative, analytical study approved by the Ethics Committee in Research on Human Beings of the Federal University of Sergipe (CAAE 38981320.2.0000.5546) with students from 10 to 18 years of age at a public school in a municipality in the Brazilian Northeast. A descriptive analysis of screen time, sociodemographic, economic variables, academic year, physical activity, sleep duration and daytime sleepiness was performed. Fisher's exact test and Pearson's chi-square test were used to analyze the independence hypothesis and the Mann-Whitney test to assess the hypothesis of equality of the median of two samples, in addition to simple and multiple logistic regression. Results: 364 students participated in the study. The eighth and ninth year of elementary school; the first and second years of high school made more excessive use of electronic devices. There is a greater chance of screen time higher than recommended in those with a higher socioeconomic level. High screen time was associated with the presence of daytime sleepiness, with a higher prevalence of excessive screen time in students who considered they rarely and often had sleepiness. Conclusions: The prevalence of excessive screen time was higher in adolescents considered older, when compared to younger ones and in those with better socioeconomic conditions. It is possible that screen time influences shorter sleep duration and the presence of daytime sleepiness.